Good practices in the promotion of geoethical values in a UNESCO Global Geopark - Brilha, J. B. (2020)
In the Arouca’s UNESCO Global Geopark (Northern Portugal) mining activities and geoconservation co-exist and together promote sustainable use of geoheritage with benefits either to local communities and to the international scientific community.